PENGARUH FAKTOR ANTHROPOMETRI DAN FISIK DOMINAN PENENTU KEMAPUAN JUMP SHOOT BOLA BASKET - Junalia Muhammad (University of Cenderawasih, 2017)
This research attemps to find the dominant phisical and antrophometry factors in determining basketball jump shoot ability. The theories in this research used : shooting, jump shoot, anthrophometry, leg muscle power, hand muscle strength, hand-eye coordination, flexibility, and jump shoot strength. This research used regretion analysis approach. The regretion analysis to measure huge of free variable impact to depend variable dan to pridicate depen variable with free variable. The subject used college student of FIK UNCEN. The instruments there are 1) stadiometer to measure body height, 2) weighting machine to measure weight body, 3) vertical jump to measure leg muscle power, 4) pushup to measure hand muscle strength, 5) wall pas to measure hand-eye coordination, 6) sit and reach to measure flexibility, and 7) 30 seconds jump shot to measure jump shoot strength. The data analysis used hyphotesis test and analysis conditional test. The result showed that 15,0% jump shot data variant got explained by body height, body weight, leg muscle strength, hand muscle power, hand-eye coordination and flexibility. The sixth valiables had significant impact to jump shoot strength simultannously, with yield p=0,000. And, the most dominant in jump-shot strength determinant is hand-eye coordination variable with highest standardized coeffient beta than other variable that is 0,621.